2011
DOI: 10.1002/ejoc.201100231
|View full text |Cite
|
Sign up to set email alerts
|

Calcium‐Catalyzed Direct Coupling of Alcohols with Organosilanes

Abstract: A calcium‐catalyzed direct substitution of π‐activated alcohols with different organosilanes under very mild reaction conditions is presented. The high reactivity of the calcium catalyst allows efficient conversion of secondary and tertiary allylic, secondary benzylic, and tertiary propargylic alcohols with allyltrimethylsilane at room temperature. Furthermore, the first direct substitution of an alcohol with (E)‐ as well as (Z)‐alkenylsilanes was achieved under mild reaction conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 26 publications
1
23
0
1
Order By: Relevance
“…A range of different secondary benzylic propargylic alcohols were reduced in reaction times of 5 to 10 min to give the desired products in good to excellent yields (Scheme ). Similarly to what was previously observed in the ruthenium and gold‐catalyzed processes,12, 13 calcium‐catalyzed propargylic reduction of secondary alcohols is limited to benzylic propargylic alcohols. Non‐benzylic propargylic alcohols were reactive under the reaction conditions but tended to form oligomeric side products thus leading to the desired products in very poor yields.…”
Section: Reactions Of Alcoholssupporting
confidence: 60%
See 1 more Smart Citation
“…A range of different secondary benzylic propargylic alcohols were reduced in reaction times of 5 to 10 min to give the desired products in good to excellent yields (Scheme ). Similarly to what was previously observed in the ruthenium and gold‐catalyzed processes,12, 13 calcium‐catalyzed propargylic reduction of secondary alcohols is limited to benzylic propargylic alcohols. Non‐benzylic propargylic alcohols were reactive under the reaction conditions but tended to form oligomeric side products thus leading to the desired products in very poor yields.…”
Section: Reactions Of Alcoholssupporting
confidence: 60%
“…Calcium‐catalyzed allylation : A further catalytic CC‐bond forming process, which appeared highly beneficial, was the direct substitution of alcohols with unsaturated organosilicon‐based carbanion surrogates (Scheme ) 12. The general utility of these water tolerant organometallic reagents is well recognized and numerous scientific efforts led to their establishment as a valuable instrument in the synthetic tool‐box.…”
Section: Reactions Of Alcoholsmentioning
confidence: 99%
“…56,57 In further pursuit towards the cost-effective methodology for propargylic substitution reaction avoiding costly transition metals, Niggemann and co-workers in the year 2011 developed an efficient calcium-catalyzed allylation of p-activated alcohols 23 with diverse silyl-based carbanions 63 under very mild reaction conditions, Scheme 25. 58 The reaction of propargylic alcohols 23 and allyltrimethylsilane 63 in presence of 5 mol% each of Ca(NTf 2 ) 2 and Bu 4 NPF 6 proceeded smoothly at room temperature in dichloromethane to give the desired allylated product 64 aer 1 h as a 2.7 : 1 mixture of allylated regioisomers in good yield. Incomplete transformation was observed with strongly coordinating solvents like ether, THF whereas dichloromethane was found to be the most suitable solvent for the allylation of propargyl alcohols.…”
Section: Calcium Derived Catalystsmentioning
confidence: 99%
“…Although on first glance, the third step in Scheme appears problematic, recent studies have shown that activated alcohols 8 (mainly benzyl or some tertiary) can be converted to allyl derivatives 9 (Scheme ) by allylsilanes using a variety of Lewis acids based on B,5 In,6 Bi,7 Fe,8 Al,9 Ca,10 Zr,11 Re,12 Rh,13 as well as Brønsted acids such as Montmorillonites14 and PMA (phosphomolybdic acid),15 either in catalytic or stoichiometric amounts. Recently, we found that TiCl 4 in dichloromethane (DCM) is more efficient than most Lewis acids and promotes, within minutes, the allylation of benzyl, allyl, as well as of some tertiary alcohols at room temperature 16…”
Section: Introductionmentioning
confidence: 99%